International research collaboration – how powerful is it really? - Sascha Duerkop; Jakob Grubmuller; Rana Badran (Journal of Construction Project Management and Innovation)
Countries that do participate in International Research Collaboration (IRC) are placed in advantageous positions to promote scientific and technological advancements. This advantage is known to be particularly high for countries outside of Europe or North America. Subsequently, international organisations do actively promote and support the emergence of collaborative research platforms, in particular in these countries. But how can the success of such a platform be measured? Do the benefits always outweigh the costs? This paper seeks to define a framework for assessing the success of a research collaborative platform. As a case study, a bilateral research platform implemented by the authors will be critically assessed.